Pengaruh Kepercayaan dan Risiko Pada Minat Beli Belanja Online - Rosihan Anwar; Wijaya Adidarma (Program Studi Magister Manajemen FE Unsri, 2016)
The use of internet and e-commerce in Indonesia grows continuously. The Internet has changed the consumer behaviour in meeting their needs. Therefore, this study aimed to determine the effect of trust in online stores and perceived risk on consumer online purchase intention. This study involved 180 internet users as respondents who have visited online shopping sites in Indonesia. The results found that consumer trust in online stores have negative effect on perceived risk in buying online. Otherwise, the trust has positive effect on online purchase intention. However, this study proves there is no risk in buying interest referring them to shop online. Furthermore, this study found that trust level of female customers to online shopping sites is higher than male customers